Successful Control of Lymphatic Filariasis in the Republic of Korea - Cheun, Hyeng-Il (The Korean Society for Parasitology, 2009)
A successful experience of lymphatic filariasis control in the Republic of Korea is briefly reviewed. Filariasis in the Republic of Korea was exclusively caused by infection with Brugia malayi. Over the past several decades from the 1950s to 2006, many investigators exerted their efforts to detection, treatment, and follow-up of filariasis patients in endemic areas, and to control filariasis. Mass, combined with selective, treatments with diethylcarbamazine to microfilaria positive persons had been made them free from microfilaremia and contributed to significant decrease of the microfilarial density in previously endemic areas. Significant decrease of microfilaria positive cases in an area influenced eventually to the endemicity of filariasis in the relevant locality. Together with remarkable economic growth followed by improvement of environmental and personal hygiene and living standards, the factors stated above have contributed to blocking the transmission cycle of B. malayi and led to disappearance of this mosquito-borne ancient disease in the Republic of Korea.